Assessment of chemical kinetic models on hypersonic flow heat transfer. (August 2017) - Wang, X.Y.; Yan, C.; Zheng, Y.K.; Li, E.L.
Highlights: The performance of chemical kinetic models for heat transfer are assesed. Three typical hypersonic vehicles are employed. The reasons for discrepancies of heat flux are explained and discussed. Abstract: The objective of this study is to assess the performance of chemical kinetic model for heat transfer acting on the hypersonic vehicle. Four different chemical kinetic models, including Dunn Kang model, Gupta model, Park 87 model and Park 91 model, are implemented and assessed. The differences among these models are obvious, consisting of the elementary reactions, the method of evaluating backward rate coefficients and chemical kinetic rates. In order to further investigate the performance of these models for hypersonic aeroheating prediction, three typical test cases are employed: (1) the heat transfer acting on ELECTRE vehicle at Mach number 13, (2) the heat transfer acting on Apollo command module at Mach number 20.5 and (3) the heat transfer acting on Space Shuttle Orbiter at Mach number 20.985. Firstly, the behaviors of these models are demonstrated by comparing the numerical results with the flight data or experimental data in detail. Secondly, the reasons for the discrepancies of heat fluxes computed with these models are discussed. The results reveal that the heat fluxes acting on ELECTRE vehicle and the head of Space Shuttle Orbiter predicted by these chemical kinetic models are in good consistency and agree well with the flight or experimental data. With the increasing of complexity of the vehicle's geometry, the differences of heat flux, especially the peak heat flux, become more and more obvious, and the maximum difference among them may exceed 25%. The numerical results also indicate that the numerical prediction of heat transfer acting on complicated geometry exhibits a relatively strong sensitivity to the choice of chemical kinetic models. The difference of chemical kinetic rates and the complicated flow structure in the flowfield may be the primary reasons for the heat flux discrepancies.